Straw in Clay Bricks and Plasters-Can We Use Its Molecular Decay for Dating Purposes? - Tintner, Johannes; Roth, Kimberly; Ottner, Franz; Syrová-Anýžová, Zuzana; Žabičková, Ivana; Wriessnig, Karin; Meingast, Roland; Feiglstorfer, Hubert (Molecules (Basel, Switzerland), 2020)
Dating of clay bricks (adobe) and plasters is a relevant topic not only for building historians in the Pannonian region. Especially in vernacular architecture in this region, clay with straw amendments is a dominant construction material. The paper presents the potential of the molecular decay of these amendments to establish prediction tools for age based on infrared spectroscopic measurements. Preliminary results revealed spectral differences between the different plant parts, especially culms, nodes, and ear spindles. Based on these results, a first prediction model is presented including 14 historic samples. The coefficient of determination for the validation reached 62.2%, the (RMSE) root mean squared error amounted to 93 years. Taking the limited sample amount and the high material heterogeneity into account, this result can be seen as a promising output. Accordingly, sample size should be increased to a minimum of 100 objects and separate models for the different plant parts should be established.
Keywords: earth construction; časové faktory; adobe construction; Spectrum Analysis; Construction Materials; konstrukční materiály; Clay; FTIR spectroscopy; straw amendments; stopové prvky; Time Factors; jíl; vernacular architecture; Trace Elements; spektrální analýza